MODEL ALAT PENAWAR AIR TANAH TERINTRUSI AIR LAUT (AIR PAYAU) DENGAN PROSES ELEKTROKOAGULASI - Danang Wijayanto; Sutanto Sutanto (Politeknik Negeri Jakarta, 2011)
Brackish water or fresh water that tastes a bit salty due to seawater mixed is a frequent problem faced by people living close to the beach area. Ground water areas near shore are often caused by sea water intrusion inland. In general, brackish water can not be used as drinking water, and less feasible to be used for much else. To be used as drinking water and appropriate for use in domestic use brackish water needs special treatment to reduce the levels of minerals in it, primarily to reduce levels of salt in it. For this purpose an equipment model has been made. This model works based on the electrocoagulation process. This electrocoagulation equipment model consists of a rectangular bathtub equipped with stirrer, and square shaped settling tanks. The sizes of electrocoagulation process tank are 20 cm length, 20 cm width and 40 cm high. Motor with capacity of 0.5 hp used to stirred, equipped with 4 pieces blades. While the sizes of settling tank are 20 cm long, 20 cm wide and 40 cm high. Performance testing of this model implemented by filling 4.5 liters of brackish water into the electrocoagulation tank and each test processed using electric current of 1 ampere, 3 amperes and 5 amperes. Observation time for each test is 40, 80, 120, 160, 200, 240, 280, 320, 360, 400, 440 and 480 minutes. Concentration measurement of magnesium and sodium for each test performed by AAS. The final results of testing showed that the use of 3 amperes electric currents is able to reduce levels of magnesium from 100,000 mg/ltr to 81 mg/ltr and reduce sodium levels from 9600 mg/ltr to 185 mg/ltr with 400 minutes operating time. Key words: Brackish Water, Minerals Content, Electrocoagulation Process, Minerals Reduction, Fresh Water ABSTRAK Air payau atau air tawar yang rasanya agak asin karena tercampur air laut merupakan masalah yang sering dihadapi oleh masyarakat yang tinggal didaerah dekat dengan pantai. Air tanah daerah dekat pantai sering bersifat payau disebabkan adanya interusi air laut ke daratan. Pada umumnya air payau tidak dapat digunakan sebagai ari minum, dan kurang layak digunakan untuk keperluan yang lain. Agar dapat digunakan sebagai air minum dan layak digunakan untuk keperluan rumah tangga sehari-hari air payau perlu perlakuan khusus yang tujuannya mengurangi kadar mineral didalamnya terutama mengurangi kadar garam. Untuk keperluan ini telah dibuat model alat yang bekerja berdasarkan proses elektrokoagulasi. Model alat terdiri atas bak proses elektrokoagulasi berbentuk persegi yang dilengkapi pengaduk dan bak pengendap berbentuk persegi. Ukuran bak proses elektrokoagulasi panjang 20 cm, lebar 20 cm dan tinggi 40 cm. Ukuran motor pengaduk adalah 0,5 hp yang dilengkapi 4 buah sudu. Sedangkan bak pengendap berukuran panjang 20 cm, lebar 20 cm dan tinggi 40 cm. Pengujian kinerja alat dilakukan dengan mengisi 4,5 liter air payau ke dalam bak proses elektrokoagulasi dan untuk setiap pengujian digunakan arus listrik 1 ampere, 3 ampere dan 5 ampere. Waktu pengamatan untuk masing-masing pengujian adalah 40,80,120,160,200,240,280,320,360,400,440 dan 480 menit. Pengukuran konsentrasi magnesium dan natrium untuk setiap pengujian dilakukan dengan AAS. Hasil akhir pengujian menunjukkan bahwa pada penggunaan arus listrik 3 amper mampu menurunkan kadar magnesium dari 100.000 mg/l menjadi 81 mg/l untuk dan kadar natrium dari 9.600 mg/l menjadi 185 mg/l dengan waktu operasi 400 menit. Kata kunci: Air Payau, Kandungan Mineral, Proses Elektrokoagulasi, Reduksi Mineral , Air Tawar